2002
DOI: 10.1074/jbc.c200348200
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of Histone H3 by COMPASS Requires Ubiquitination of Histone H2B by Rad6

Abstract: . To learn about the mechanism of histone methylation, we surveyed the genome of the yeast Saccharomyces cerevisiae for genes necessary for this process. By analyzing ϳ4800 mutant strains, each deleted for a different non-essential gene, we discovered that the ubiquitin-conjugating enzyme Rad6 is required for methylation of lysine 4 of histone H3. Ubiquitination of histone H2B on lysine 123 is the signal for the methylation of histone H3, which leads to silencing of genes located near telomeres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
420
5
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 497 publications
(452 citation statements)
references
References 25 publications
21
420
5
6
Order By: Relevance
“…We now know that monoubiquitination of H2B is required for H3K4 di-and trimethylation in yeast and that this crosstalk pathway is highly conserved from yeast to human [6,40,41]. Although the past several years brought about a watershed of information regarding the factors/proteins required for proper H2B monoubiquitination [6,[40][41][42][43][44][45][46][47][48], the molecular mechanism for this histone crosstalk was poorly understood. Recent studies in yeast S. cerevisiae demonstrated that monoubiquitination of histone H2B regulates COMPASS' compositional assembly, and therefore, proper H3K4 methylation [49].…”
Section: H2b Monoubiquitination Crosstalk In H3k4 Methylationmentioning
confidence: 99%
“…We now know that monoubiquitination of H2B is required for H3K4 di-and trimethylation in yeast and that this crosstalk pathway is highly conserved from yeast to human [6,40,41]. Although the past several years brought about a watershed of information regarding the factors/proteins required for proper H2B monoubiquitination [6,[40][41][42][43][44][45][46][47][48], the molecular mechanism for this histone crosstalk was poorly understood. Recent studies in yeast S. cerevisiae demonstrated that monoubiquitination of histone H2B regulates COMPASS' compositional assembly, and therefore, proper H3K4 methylation [49].…”
Section: H2b Monoubiquitination Crosstalk In H3k4 Methylationmentioning
confidence: 99%
“…The first breakthrough came with the identification of the budding yeast protein Bre1 [38,39], which, together with the ubiquitin-conjugating enzyme Rad6, serves as the E3 ligase in the monoubiquitylation of the yeast histone H2B on lysine 123 (K123) within transcribed chromatin [38][39][40][41]. Notably, H2B monoubiquitylation was subsequently found to be required for di-and trimethylation of lysine 4 and lysine 79 of histone H3 at transcribed chromatin [42][43][44][45][46][47][48]. This pathway is conserved from yeast to mammals, and is dependent on a host of additional proteins that converge at the elongating RNA Pol II [41,[49][50][51][52][53][54].…”
Section: Monoubiquitylated Histone H2bmentioning
confidence: 99%
“…Yeast deleted for RAD6 or BRE1, or carrying the K123R H2B mutant, display reduced GAL gene activation (Kao et al, 2004), as well as defects in meiosis (Robzyk et al, 2000;Yamashita et al, 2004), gene silencing (Dover et al, 2002;Sun and Allis, 2002), and histone H3 methylation (Dover et al, 2002;Sun and Allis, 2002), but are nonetheless viable. Our finding that there are multiple ubiquitylation events on histone H2B raises the important point that previous analyses of the functional consequences of Rad6 -Bre1-dependent H2B ubiquitylation (at K123) have been performed within a backdrop of other H2B-ubiquitylation events, which in turn may mask effects resulting from loss of Rad6 -Bre1 ubiquitylation.…”
Section: Ubiquitylation Of Lysine 123 Of H2b Can Be Essentialmentioning
confidence: 99%
“…H2B ubiquitylation is reportedly higher at active genes than at the silenced telomeres (Emre et al, 2005), and both the recruitment and activity of the H2B-ubiquitylation machinery are regulated by interactions with the transcriptional apparatus, including pol II (Xiao et al, 2005), the Paf complex (Ng et al, 2003;Wood et al, 2003b;Xiao et al, 2005), and Bur kinases (Wood et al, 2005). At active genes, H2B ubiquitylation is essential for the processive methylation of histone H3 at lysine residues K4 and K79 (Dover et al, 2002;Sun and Allis, 2002;Dehe et al, 2005;Shahbazian et al, 2005), but not K36 (Li et al, 2003;Wood et al, 2003b), and for recruitment of proteasomal ATPases to chromatin (Ezhkova and Tansey, 2004). Although only ϳ10% of steady-state H2B is monoubiquitylated (Robzyk et al, 2000), it is likely that a much larger percentage of H2B is actually ubiquitylated and that deubiquitylation is an active and crucial process (reviewed in Emre and Berger, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation